2017
DOI: 10.1556/2006.6.2017.084
|View full text |Cite
|
Sign up to set email alerts
|

Measures of behavioral function predict duration of video game play: Utilization of the Video Game Functional Assessment – Revised

Abstract: BackgroundInternet gaming disorder (IGD) was introduced in the DSM-5 as a way of identifying and diagnosing problematic video game play. However, the use of the diagnosis is constrained, as it shares criteria with other addictive orders (e.g., pathological gambling).AimsFurther work is required to better understand IGD. One potential avenue of investigation is IGD’s relationship to the primary reinforcing behavioral functions. This study explores the relationship between duration of video game play and the rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…By using logistic regression, a positive correlation between the Monothetic GAS score and Polythetic Partial GAS score with Daily gaming time was evidenced, in agreement with other studies [25,34,47]. This correlation was not present with the Polythetic Global GAS score; in this case, it was shown that Daily game frequency and Education level were a positive and negative predictor of Polythetic Global GAS score, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By using logistic regression, a positive correlation between the Monothetic GAS score and Polythetic Partial GAS score with Daily gaming time was evidenced, in agreement with other studies [25,34,47]. This correlation was not present with the Polythetic Global GAS score; in this case, it was shown that Daily game frequency and Education level were a positive and negative predictor of Polythetic Global GAS score, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…However, there is still an open debate to identify addiction syndrome in comparison to behavioral dependence in a more specific way in order not to pathologize common behaviors [24]. Furthermore, it is not yet clear how behaviors considered pathological can be related to the duration of the game, or how to understand the seriousness of dependent behaviors [25]. This association is due to the fact that a gaming disorder shares many features with addictions related to psychoactive substances and with gambling disorder [26].…”
Section: Introductionmentioning
confidence: 99%
“…The VGFA-R sub-scores demonstrated meaningful gender differences in the present study. In particular, previous research 19,20 has indicated the escape-maintained function of online gaming (i.e., avoiding school/job responsibilities) is significantly correlated with number of hours played weekly.…”
Section: Discussionmentioning
confidence: 99%
“…Participants completed the Video Game Functional Assessment-Revised (VGFA-R) on a 24-item Likert scale that assesses four functions that sustain videogame play: (i) social attention, (ii) tangible/intangible rewards, (iii) escape/avoidance of demands or pain, and sensory stimulation (Buono et al, 2016) 20 . The assessment comprised one of seven responses indicating degrees of agreement or disagreement to the statement (1=Never, 2=Almost never, 3=Seldom, 4=Half of the time, 5=Usually, 6=Almost always, 7=Always).…”
Section: Methodsmentioning
confidence: 99%
“…Time is an important concept when playing games that could be motivated or disrupted by tangible things. It shows that time inside the game is a matter that could make players become more addicted or could prevent/mitigate the addiction [17]. Meaning, it also shows that the time factor inside the game could whether drive addiction or prevent/mitigate the addiction element inside the game.…”
Section: Literature Reviewmentioning
confidence: 96%